PENGARUH PROMOSI DAN FASILITAS TERHADAP LOYALITAS MELALUI VARIABEL INTERVENING KEPUASAN PENGUNJUNG PADA HOTEL RENGGANIS PASIR PUTIH KABUPATEN SITUBONDO - Habibarrahman, Moh Fathoni; Kusnadi, Edi; Fandiyanto, Randika (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
The more rapid and growing tourism in Pasir Putih, Situbondo Regency, allows many visitors, especially tourists who need a resting place. Moreover, supported by various tourist attractions that are quite good, this has become the basis for business development in the lodging service sector in Situbondo. Hotel Rengganis is one of the lodging service businesses in Pasir Putih, Situbondo Regency that offers a resting place, by providing bedroom facilities, food, and drinks for people who are doing business or recreation, in order to provide a peaceful, comfortable, healthy and friendly atmosphere that required by consumers or guests. The purpose of this study was to analyze and examine the effect of promotions and facilities on loyalty through visitor satisfaction as an intervening variable. The sampling technique used was saturated sampling technique. Data analysis and hypothesis testing in this study used the Structural Equation – Partial Least Square (PLS-SEM) model. The results of the direct influence hypothesis test using the smart PLS 3.0 application, show that Promotion has a significant positive effect on visitor satisfaction, Facilities have a significant positive effect on visitor satisfaction, Promotion has a positive but not significant effect on Loyalty, Facilities have a significant positive effect on Loyalty, Visitor satisfaction has a significant positive effect to Loyalty. The results of the indirect effect hypothesis test show that the Promotion variable on Loyalty through Visitor Satisfaction has a significant positive effect, Facilities on Loyalty through Visitor Satisfaction have a significant positive effect